Job Satisfaction and Work Engagement among Civil Servants in a 3T Region: A Correlational Study in West Halmahera Indonesia - Elisabeth Prayshe Eni; Susana Prapunoto (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Although the relationship between job satisfaction and work engagement has been widely studied, empirical evidence in the public sector within underdeveloped, frontier, and outermost (3T) regions remains limited. This gap is particularly evident in West Halmahera, a region with geographical challenges that may influence the work experiences of civil servants. This study aims to examine the relationship between job satisfaction and work engagement among civil servants at Office X, West Halmahera. The study employed a quantitative correlational approach with a cross-sectional design, involving 341 civil servants selected through purposive sampling with a minimum of two years of work experience as the criterion. Data were collected using the Job Satisfaction Survey (JSS) and the Utrecht Work Engagement Scale-9 (UWES-9). Because the data were not normally distributed, Spearman’s rho correlation analysis was used. The results indicated a significant positive relationship between job satisfaction and work engagement (r = .321; p < .001), with the strength of the relationship ranging from weak to moderate. Descriptively, most respondents were in the high category of job satisfaction (56.3%) and high work engagement (83.6%). These findings are expected to contribute to the development of industrial and organizational psychology literature in the public sector, particularly within the context of 3T regions. Keywords: job satisfaction, public sector, work engagement, 3T region